On the Question of the Powers of the Federal Executive Authorities of Germany in the Field of Genetic Engineering - E. A. Lebedeva (Сибирское юридическое обозрение, 2020)
At the present stage of the development of genetic engineering activities in the Russian Federation the question of the expediency of distributing powers between federal executive bodies and executive bodies of constituent entities is relevant. In this regard, the experience of Germany in securing the relevant powers in the field of genetic engineering for the executive authorities is considered, in particular, the powers of the federal executive authorities of Germany are examined to release and place genetically modified organisms, to monitor the impact of artificial microorganisms on human health and the environment, as well as administrative functions for maintaining information registers of information about modified organisms. The Author analyzes the powers of the German Federal Ministry of Food and Agriculture (German: Bundesministerium für Ernährung und Landwirtschaft – BMEL), the Federal Office for Consumer Protection and Food Safety of Germany (German: Bundesamt für Verbraucherschutz und Lebensmittelsicherheit – BVL) and other bodies. In addition, the Author has investigated the powers of the federal states of the Federal Republic of Germany in the field of genetic engineering work related to the use and production of artificial microorganisms and GM products. As an example, the competence of the authorized body of the federal state of Hesse – the Department of the Government of Hesse for genetic engineering – is considered. Analysis of the powers of the executive authorities of Germany in the field of genetic engineering made it possible to formulate conclusions and recommendations for streamlining the powers of executive authorities and organizations in Russia. As a result, proposals were made to improve public administration in the field of genetic engineering activities in Russia, including the need to entrust a separate authority with the authority for comprehensive regulation in the field of genetic engineering activities, as well as the inexpediency of currently providing executive the authorities of the constituent entities of the Russian Federation, the powers to exercise public administration in the area under consideration.